The Role Of Financial Literacy And Digital Innovation In Improving Business Performance And Sustainability Of Business Actors In Kampong Melayu Tourism Village Pontianak City - Windi Pratiwi; Aisyah Aisyah; Muchammad Ariffin (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose of this study is to determine how financial literacy and digital innovation contribute to business performance and sustainability. The number of samples taken using purposive sampling method using probability, and quota samples were used to divide 170 respondents into various businesses. SEM-PLS (Partial Least Square) analysis technique was used to analyze the data, which consists of flow analysis and descriptive analysis. The results show that financial literacy and digital innovation play an important role in improving business performance and business sustainability. Financial literacy has a positive impact on business performance (24.8%) and business sustainability (11.3%), while digital innovation has a greater impact, affecting business performance by 50.4% and business sustainability by 22%. In addition, financial literacy and digital innovation indirectly influence business sustainability